A Review on Past, Present and Future of Ethnobotany in India: A Comprehensive Review of Ethnobotany in India: Past, Present, and Future (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Ethnobotany was worked to incorporate plant concentrates as well as investigations of green growth, lichens, and parasites. It is firmly connected with the science of scientific classification, pharmacognosy, phytochemistry, environment, and preservation. So as to feature the therapeutic utilization of plants and there pharmacological angles, this article audits various ethnobotany messages and papers, and furthermore clarifies the extent of ethnobotany. It incorporates a concise survey of ethnobotany in India, onpast, present and future.